ANALYSIS OF THE EFFECTIVENESS OF PEDESTRIAN CROSSING BRIDGE (JPO) FACILITIES IN BANJARBARU CITY - Fadhilah, Erwin Rony; Widayanti, Nova (Universitas Lambung Mangkurat, 2026)
People crossing bridges serve as a means to reduce conflicts between pedestrians and vehicles, which can interfere with the smooth flow of traffic, as well as improve safety and comfort when crossing. One of the roads in Banjarbaru that uses access to cross people, namely on Ahmad Yani KM 34 street, precisely adjacent to the Banjarbaru City BNI office. This pedestrian crossing bridge is newly built by the government, this is done based on consideration of the need for transportation crossing facilities/infrastructure in the city of Banjarbaru. This study was conducted to evaluate the performance of the use of pedestrian bridges in Banjarbaru City by considering the frequency of crossings (P), traffic intensity (V), and evaluations from participants. The level of effectiveness of the use of pedestrian bridges is classified as